Keunggulan dan Kelemahan Program Akselerasi di SMA: Tinjauan Psikologi Pendidikan - Alsa, Asmadi (ANIMA Indonesian Psychological Journal, 2007)
The establishment of the acceleration program for the elementary, junior high, and senior high school reflects the special attention of the government towards education for smart and special gifted students. The acceleration program has its own superiority as well as weaknesses, which are different from the regular program. To respond to the various anxieties related to the negative effect of the acceleration program, the author exposes various superiorities and weaknesses based on the theoretical review, integrated with the empirical reports from accelerated senior high school classes in Indonesia. A proposal to improve the curriculum, the human resource potential, and the operational technique are also discussed. Penyelenggaraan program akselerasi bagi siswa SD, SMP, dan SMA merupakan bentuk perhatian khusus Pemerintah Indonesia terhadap pendidikan siswa cerdas dan berbakat istimewa. Program akselerasi memiliki keunggulan dan kelemahan tersendiri yang berbeda dengan program reguler. Untuk menanggapi berbagai kekhawatiran terkait dampak negatif program akselerasi, peneliti memaparkan berbagai keunggulan dan kelemahan berdasarkan kajian teoretik yang dipadukan dengan laporan empiris dari kelas-kelas SMA akselerasi di Indonesia. Usulan perbaikan kurikulum, sumber daya manusia, serta teknis operasional juga dibahas.